The Effect of Freedom of Learning Policy and Work Discipline on Teacher Performance with Teacher Competence as an Intervening Variable in SMA Esa Prakasa Langkat Regency - Dedy Purnama; Kiki Farida Ferine (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of the Free Learning Policy and Work Discipline on Teacher Performance with Teacher Competence as an Intervening Variable. The research was conducted at Prakasa High School, Langkat Regency. The population in this study was a sample of 80 teachers. The sample technique used is a saturated sample. Data collection was carried out by distributing questionnaires. The research model used is Path Analysis and Smart PLS as measurement tools. The results of this study are that work discipline has a positive and significant effect on teacher performance. Work Discipline has a positive and significant effect on Teacher Competence. Teacher competence has a negative and insignificant effect on teacher performance. Merdeka Learning has a positive and significant effect on teacher performance. Merdeka Learning has a positive and significant effect on Teacher Competence. Work Discipline has an effect on Teacher Performance through teacher competence which has no significant negative effect. Merdeka Belaja has an insignificant negative effect on teacher performance through teacher competence.